2004
DOI: 10.1381/0960892041590999
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Surgery: Shedding the Monetary Weight of Prescription Costs in the Managed Care Arena

Abstract: RYGBP can decrease the prescription medication requirements, resulting in significant cost-savings in the treatment of obesity-related hypertension and diabetes. This study found a 77.3% reduction in total cost of diabetic and anti-hypertensive medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 23 publications
2
42
0
1
Order By: Relevance
“…It also confirms the decrease in postsurgical costs of outpatient pharmacy as reported by others [16,26,27]. Like other reports, it suggests that bariatric surgery is costeffective [12-14, 28, 29].…”
Section: Discussionsupporting
confidence: 88%
“…It also confirms the decrease in postsurgical costs of outpatient pharmacy as reported by others [16,26,27]. Like other reports, it suggests that bariatric surgery is costeffective [12-14, 28, 29].…”
Section: Discussionsupporting
confidence: 88%
“…Maciejewski et al 26 reported that there was a 50% reduction in the use of antidiabetic drugs within one year after bariatric surgery. Additionally, Potteiger et al 27 and Narbro et al 28 reported that there were significant reductions in the numbers and cost of drugs used to treat diabetes relating to obesity, after surgery. Importantly, the features of the population and the follow-up period need to be taken into account in assessing these proportions, because the impact of surgery on antidiabetic drug use may vary according to these factors.…”
Section: Antidiabetic Drugsmentioning
confidence: 99%
“…45,46 Regarding the reduction in the number of patients who were using antihypertensive drugs, our findings were similar to those reported by other authors. [26][27][28]47,48 Partial or complete improvement was shown within 12 months after undergoing bariatric surgery, especially among the patients who had undergone gastric bypass, 10,47 thus reducing the need for antihypertensive drugs. 49,50 It seems again that our results were somehow related to the technique used for the majority of our patients, i.e.…”
Section: Antihypertensive Drugsmentioning
confidence: 99%
“…1 The high morbidity rate is costly, both for the individual and the health-care system. [2][3][4] Weight loss improves or resolves the co-morbidities. 5,6 Bariatric surgery, by restrictive or malabsorptive methods, is the only treatment sustaining weight loss.…”
Section: Introductionmentioning
confidence: 99%